Antifungal Activity of Crude Extracts of Ageratum conyzoides, Cyperus rotundus, and Amaranthus spinosus Against Rust Disease - Eriyanto Yusnawan; Alfi Inayati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Puccinia arachidis is an obligate pathogen which infects peanut leaves and causes rust disease. Alternative controls of this disease, particularly to limit the frequent use of synthetic fungicide, have been conducted. One of which is by applying botanical fungicides. Crude extracts of Ageratum conyzoides, Amaranthus spinosus, and Cyperus rotundus were used to suppress the rust disease intensity on Bima peanut cultivar. A. conyzoides extracts at 2.5% and 5.0% concentrations were the most effective biofungicide to reduce the disease. The disease intensity (29.8 % and 30.2 %) recorded at 10 weeks after planting (WAP) was significantly lower than the untreated crops (41.4 %). Both weed extract applications reduced about 50 % of pustule number compared to untreated crops at 10 WAP. Applications of 2.5 % and 5.0 % of ageratum extracts saved yield loss of 67.5 % and 63.5 %. Caryophyllene was observed in the roots, stems, leaves, and flowers of ageratum extracts in considerable amounts based on GC-MS analysis and may attribute to its significant antifungal activity. Higher total phenolic and flavonoid contents were observed in ageratum extracts than in amaranthus and cyperus extracts. Ageratum extracts at concentrations of 2.5 % to 5 % could be used to control peanut rust disease.